Digital innovation strategies for intangible cultural heritage preservation and creative products: Focusing on traditional Chinese new year woodblock printing - Jiang, Yuandi; Yu, Ziwei; Pashkevych, Kalyna (Research Journal in Advanced Humanities, 2025)
Purpose: This study aims to explore the impact of digital innovation strategies on cultural heritage preservation and the development of creative products, focusing on traditional Chinese New Year woodblock printing in China. Specifically, it investigates the mediating role of digital literacy and the moderating effect of the perceived value of intangible cultural heritage in these relationships.Method: A quantitative research design was employed, utilizing a structured online survey to collect data from 227 respondents involved in the cultural heritage and creative industries in China. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to test the hypothesized relationships between digital innovation strategies, digital literacy, perceived value, cultural heritage preservation, and creative products.Findings: The findings indicate that digital innovation strategies significantly influence both cultural heritage preservation and creative product development. Digital literacy was found to mediate these relationships, while the perceived value of intangible cultural heritage moderated the effects of digital innovation on both preservation and creative product outcomes. These results underscore the importance of digital tools and strategies in enhancing cultural heritage practices and creative industries.Originality/Implications: This research contributes to the understanding of how digital innovation can bridge the gap between cultural heritage preservation and creative industries. It provides practical insights for policymakers, cultural institutions, and stakeholders in creative sectors, emphasizing the need for digital literacy and greater engagement with intangible cultural heritage in digital transformation efforts.